2018
DOI: 10.1155/2018/7683929
|View full text |Cite
|
Sign up to set email alerts
|

Image Theory for Neumann Functions in the Prolate Spheroidal Geometry

Abstract: Interior and exterior Neumann functions for the Laplace operator are derived in terms of prolate spheroidal harmonics with the homogeneous, constant, and nonconstant inhomogeneous boundary conditions. For the interior Neumann functions, an image system is developed to consist of a point image, a line image extending from the point image to infinity along the radial coordinate curve, and a symmetric surface image on the confocal prolate spheroid that passes through the point image. On the other hand, for the ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…It will be interesting to extend the analysis to the case of a spheroid or cylinder [38][39][40][41][42]. Since the main effect of confinement is a volume reduction, one can use the results for a three-dimensional cuboid to estimate the overall influence of confinement on protein synthesis rates, even for cells with a spheroid or cylindrical shape.…”
Section: Three-dimensional Cuboidmentioning
confidence: 99%
“…It will be interesting to extend the analysis to the case of a spheroid or cylinder [38][39][40][41][42]. Since the main effect of confinement is a volume reduction, one can use the results for a three-dimensional cuboid to estimate the overall influence of confinement on protein synthesis rates, even for cells with a spheroid or cylindrical shape.…”
Section: Three-dimensional Cuboidmentioning
confidence: 99%
“…coordinate line, to imitate the line image for the sphere problem, but they still needed to correct for this by adding a surface charge on an ellipsoidal surface that encloses the point and line image. This image formulation is specialized for the prolate spheroid in [8]. A recent paper [9] suggested that the best image solution may be to use Sommerfeld images which are placed in a second copy of R 3 , attached at the surface.…”
Section: Introductionmentioning
confidence: 99%
“…For the non-rotational ellipsoid with Neumann boundary condition, the first attempt at finding an image solution is in [46], where they assumed a point image plus a curved line of image charge extending along a spheroidal coordinate line, but they still needed to correct for this by adding a surface charge on an ellipsoidal surface that encloses the point and line image. This image formulation is specialized for the prolate spheroid in [47].…”
Section: Conducting Spheroidmentioning
confidence: 99%